2020
DOI: 10.1371/journal.ppat.1008381
|View full text |Cite
|
Sign up to set email alerts
|

HIV infects astrocytes in vivo and egresses from the brain to the periphery

Abstract: HIV invades the brain during acute infection. Yet, it is unknown whether long-lived infected brain cells release productive virus that can egress from the brain to re-seed peripheral organs. This understanding has significant implication for the brain as a reservoir for HIV and most importantly HIV interplay between the brain and peripheral organs. Given the sheer number of astrocytes in the human brain and their controversial role in HIV infection, we evaluated their infection in vivo and whether HIV infected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
113
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(132 citation statements)
references
References 71 publications
7
113
0
1
Order By: Relevance
“…Thus, to the best of our knowledge, this is the first report directly comparing two different HIV-1 Tat induction methods to evaluate changes in behavior and gene expression in a rodent model. We showed that Tat induction in iTat mice led to mild behavioral deficits when compared to WT controls including one or more of the following trends [1] higher anxiety levels depicted by reduced time spent in the open arms of EPM [2] altered ambulation during LMA [3] higher swim speeds in MWM [4] altered learning in T-maze. Simultaneously, we also depicted that gene expressions of [1] select inflammatory cytokines were unchanged, [2] MMPs were elevated, [3] TIMPs were altered depending on the duration of Tat exposure, subsequently impacting the brain MMP/TIMP balance.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Thus, to the best of our knowledge, this is the first report directly comparing two different HIV-1 Tat induction methods to evaluate changes in behavior and gene expression in a rodent model. We showed that Tat induction in iTat mice led to mild behavioral deficits when compared to WT controls including one or more of the following trends [1] higher anxiety levels depicted by reduced time spent in the open arms of EPM [2] altered ambulation during LMA [3] higher swim speeds in MWM [4] altered learning in T-maze. Simultaneously, we also depicted that gene expressions of [1] select inflammatory cytokines were unchanged, [2] MMPs were elevated, [3] TIMPs were altered depending on the duration of Tat exposure, subsequently impacting the brain MMP/TIMP balance.…”
Section: Discussionmentioning
confidence: 93%
“…During the antiretroviral therapy (ART) era, the brain remains a viral reservoir for HIV (1)(2)(3), and milder forms of HIV-associated neurocognitive disorders (HAND) affect nearly 18 million HIVinfected individuals lowering the quality of life (4)(5)(6)(7). Patients suffering from these milder forms of HAND exhibit difficulty with working memory, executive functioning, and speed of information processing (6).…”
Section: Introductionmentioning
confidence: 99%
“…HIV-1 Tat is a regulatory protein that is released and efficiently taken up by many cell types including astrocytes [ 5 ]. Astrocytes are extensively infected with HIV-1, and these cells also act as a “safe heaven” for the latent form of the virus [ 6 , 7 ]. In addition, the clinical reports also reveal the presence of HIV-1 Tat protein in the cerebrospinal fluid (CSF) from the infected patients successfully treated with cART [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, most data support that astrocytes can be infected by HIV, release high levels of inflammatory factors and produce several viral proteins including Tat, Nef, and Rev, which promote inflammation and damage to surrounding cells (Ferrell and Giunta, 2014 ; Hong and Banks, 2015 ). In fact, recent studies propose that astrocytes infected with HIV in addition to releasing viral proteins, may also release infectious virions that can infect T-cells in the brain that can then be trafficked to the periphery (Lutgen et al, 2020 ).…”
Section: Astrocytes and Hivmentioning
confidence: 99%